Effect of austenitic stainless steel cladding on the high-temperature oxidation resistance of ferritic 2.25Cr-1Mo (Grade 22) steel using the SMAW process - Jafarikhorami, Hassan (Journal of Composites and Compounds, 2021)
The high-temperature oxidation resistance of low alloy steel affected by the cladding of austenitic stainless steel has been investigated in this study. For this purpose, Shielded Metal Arc Welding (SMAW) technique was used to prepare a proper layer of AISI347 on the surface of ferritic steels. The microstructure and morphology properties of the alloys were examined using transmission electron microscopy (TEM), scanning electron microscopy (SEM), and Energy Dispersive X-Ray Analysis (EDX) techniques. Results demonstrated that the construction of oxide shells on the surface of non-modified ferritic steel was responsible for its low resistance in contrast to the oxidation at high-temperature conditions. The oxidation screening of coated and uncoated samples with tuning time at constant temperature showed the increased oxidizing intensity of both materials. Conversely, with tuning temperature from 850 to 950 oC at a constant time, an abnormal increase was observed in oxidation intensity. The corresponding kPs of the uncoated sample was determinate 1.27708×10-8, 3.267×10-8, and the corresponding kPs of coated material was determinate 54.5×10-10, 6.6×10-10. The performed investigation proved that the formation of oxidized compact needle microstructures in the resulting alloy is the reason for the extraordinarily oxidizing resistance of austenitic stainless steel.